Vehicle Routing at Otto's Discount Brigade - Drake, Matthew (PH Professional Business, 2014)
This new business analytics case study challenges readers to optimize the logistics operation for a regional chain of discount stores, gaining the insight they need to consolidate routes and eliminate overspending. Crystallizing realistic analytical challenges faced by companies in many industries and markets, it exposes readers to the entire decision-making process, providing opportunities to perform analyses, interpret output, and recommend the best course of action. Author: Matthew J. Drake, Duquesne University.